Chemotherapy and survival in advanced breast cancer: the inclusion of doxorubicin in Cooper type regimens. - A'Hern, R. P. (Nature Publishing Group, 1993)
The value of the inclusion of doxorubicin hydrochloride (dox) in Cooper type regimens in advanced breast cancer was assessed by performing an overview employing summary statistics derived from published papers of randomised clinical trials comparing Cooper type regimens that contain dox with regimens in which dox was replaced by one or more compounds. Trials were selected which published data on survival, time to treatment failure and response rate. This study suggests that dox confers advantages on all of these endpoints and that the size of such benefits needs to be taken into account when deciding whether to use dox.